Perbandingan Dimensi Mistis dan Dialogis dalam a Common Word menurut Caner Dagli dan John Chryssavgis - Akhiyat, Akhiyat (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2012)
Religion becomes a way to create such a peaceful condition for human being. In the meantime, pluralism constitutes an undistracted phenomenon which has wrapped human life for any single day. Human live in pluralism and constitutes a part of pluralism either passively or actively. Religious pluralism constitutes a particular challenges faced by world religions at this time. Understanding transcendental mission among religious followers, especially Jews, Christians and Muslim, is un-prevented phenomenon which has created several conflicts based on hatreds and fear. Each religion has been growing within heterogenic environment. Responding the realm of heterogeneity in the global era, we need principally reconciliation. It occurs in the guidance of A Common Word which is practiced as a road map to make religious dialogue and to build peace.  Religious dialogue must be practiced to reduce conflict and theological problem among religious believers. It needs applied approach to solve religious conflict. This article will elucidate the agreed principles in the field of mysticism and attempt to look for the “melting pot” of religions. The similar perception, equal understanding and tolerance will hopefully shape harmony, peace, and fairness among religious believers, among nations.